Neuroprotection of reduced thyroid hormone with increased estrogen and progestogen in postpartum depression. Issue 9 (3rd September 2019) - Li, Dan; Li, Yangyao; Chen, Yun; Li, Haiyan; She, Yuqi; Zhang, Xialan; Chen, Shuang; Chen, Wanying; Qiu, Guodong; Huang, Haiqing; Zhang, Shuyao
Abstract : Background: Postpartum depression (PPD) is a common serious mental health problem. Recent studies have demonstrated that hormone therapy serves as a promising therapeutic approach in managing PPD. The present study aims at exploring the role of thyroid hormone (TH), estrogen and progestogen in patients with PPD. Methods: Initially, PPD patients were enrolled and a PPD mouse model was established. The serum levels of estradiol (E2), progesterone (P), triiodothyronine (T3), thyroxine (T4), free triiodothyronine (FT3), free thyroxine (FT4), and thyroid-stimulating hormone (TSH) were subsequently measured. Next, in order to identify the effects of TH, estrogen and progestogen on PPD progression, mice were administrated with E2, P, contraceptives (CA), Euthyrox and methimazole (MMI). Besides, the body weight, activities, basolateral amygdala (BLA) neuron cell structure and the related gene expression of mice were analyzed. Results: The PPD patients and the mice showed elevated serum levels of T3, T4, FT3 and FT4 along with diminished E2, P and TSH levels. In the mice administered with a combination of E2, P, and MMI, decreased TH and increased estrogen and progestogen were detected, which resulted in increased body weight, normal activities, and BLA neuron cell structure. Moreover, brain-derived neurotrophic factor (BDNF) and cAMP-responsive element-binding protein (CREB) were both up-regulated in PPD mice administrated with a combination of E2, P, and MMI, which was accompanied by decreased TH and elevated estrogen and progestogen. Conclusion: Taken together, reduced TH combined with enhanced estrogen and progestogen confers neuroprotection in PPD, highlighting a potential target in prevention and treatment of PPD.